Globwood: Cellulose-glue binder for cordwood masonry - Stålhammar, Olof (My University, 2025)
Wood masonry is a building technique category that has existed in Europe and North America since the 1800s (Hagman, 2014); there are multiple names including cordwood masonry, stovewood masonry, and plank masonry that all describe similar and overlapping techniques. Cutoffs from the timber industry, stovewood, and reused materials can be used with a binder, primarily clay in Europe, or cement or lime mortars in North America to form walls. The walls can be load-bearing or be used as an infill in a load-bearing frame. This thesis investigates alternative wood-based binders made from rest products from the wood industry to use in contemporary wood masonry construction with particular focus on hiking shelters along trails in Haninge through model making and testing of different recipes. The binders are tested for density, shrinking, and environmental stability. A woodbased binder could have better insulating properties than clay, cement, or lime mortars allowing for buildings with better thermal properties while having a lower carbon footprint than existing binders. This thesis finds that a binder using papier mache mixed with sawdust and lignin provides a good mix of strength and low shrinking. Experiments showcase that binders with a higher lignin content are more resistant to environmental effects. The density of the binder mixtures suggest that binders with higher lignin content are stronger but have worse insulating properties than binders with correspondingly higher sawdust content. The material is applied in the proposal of a hiking shelter and sauna, where the building technique is used in both traditional and novel ways..
Keywords: Cordwood masonry; stovewood; vernacular; sustainable structures; hiking shelters